1996
DOI: 10.1074/jbc.271.13.7309
|View full text |Cite
|
Sign up to set email alerts
|

Heme Iron Reduction and Catalysis by a Nitric Oxide Synthase Heterodimer Containing One Reductase and Two Oxygenase Domains

Abstract: Inducible nitric oxide (NO) synthase (iNOS) is com-prised of an oxygenase domain containing heme, tetrahydrobiopterin, the substrate binding site, and a reductase domain containing FAD, FMN, calmodulin, and the NADPH binding site. Enzyme activity requires a dimeric interaction between two oxygenase domains with the reductase domains attached as monomeric extensions. To understand how dimerization activates iNOS, we synthesized an iNOS heterodimer comprised of one fulllength subunit and one histidine-tagged sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
83
0
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 29 publications
10
83
0
2
Order By: Relevance
“…This is similar to the results obtained by Siddhanta et al using iNOS heterodimers (15,16). They demonstrated that a single reductase domain is sufficient to support heme reduction and NO formation activity at one heme site.…”
Section: Effect Of the E592a Mutation On Electron Transfer And Dimersupporting
confidence: 91%
See 2 more Smart Citations
“…This is similar to the results obtained by Siddhanta et al using iNOS heterodimers (15,16). They demonstrated that a single reductase domain is sufficient to support heme reduction and NO formation activity at one heme site.…”
Section: Effect Of the E592a Mutation On Electron Transfer And Dimersupporting
confidence: 91%
“…Preparation of Heterodimers-Essentially we followed the method developed by Dr. D. Stuehr (15,16). The full-length nNOSs and the oxygenase domain dimers were dissociated into monomers by incubation with 3 M urea in buffer C containing 1% Tween 20 and 2 mM ␤-ME for 1.5 h at 25°C and then for 1 h at 0°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To become active, two NOS polypeptides must form a homodimer (11)(12)(13)(14). Dimerization creates an extensive interface between two oxygenase domains, creates high affinity binding sites for (6R)-tetrahydrobiopterin (H4B) and Arg in each oxygenase domain, and enables electrons to transfer between NOS flavin and heme groups (15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Nitric Oxide (No)mentioning
confidence: 99%
“…This last step is rate-limiting (Miller et al, 1999), occurs in trans, from the NOSred of one polypeptide to the NOSox of the other. This step is triggered by conformational changes that are induced by Ca 2+ /CaM binding (Siddhanta et al, 1996).…”
Section: Ros and Nitric Oxide Synthasementioning
confidence: 99%